Enhancing automotive embedded systems with FPGAs - Shanker, Shreejith (2016)
Modern vehicles represent a complex distributed cyber-physical system that simultaneously handles critical functions like drive-by-wire systems, non-critical functions like window/door control, and compute intensive multimedia functions. Distributed electronic control units (ECUs), which integrate processing elements and supporting peripherals (network interfaces, memory), implement a variety of functions in software, and information is exchanged between ECUs and sensors/actuators over in-vehicle networks. As the complexity of applications rises with increasing automation, extensive hardware support is required in the form of multicore processors or special purpose hardware accelerators to offer required levels of performance. Additional features also drive an increase in the number of ECUs since new functions are rarely consolidated on existing ECUs. Furthermore, network interfaces implemented as ASICs or dedicated logic must be adapted to handle increased communication loads, consuming power and requiring more infrastructure support in terms of cabling and weight. The increasing number of safety-critical functions further impacts complexity if existing one-to-one redundancy schemes are applied. Rising automation also poses news challenges like security, with researchers showing that internal networks are easily manipulated with catastrophic effects and total loss of control. Our research aims to address these challenges using architectural enhancements that are transparent at the computational and network levels, leveraging the capabilities of reconfigurable hardware. We present advanced ECU architectures with extended network capabilities, apply these in the context of safety critical systems, explore ways of extending these schemes to offer advanced security features, and show how such advanced systems can be validated in hardware. Our work represents an advancement in the state of the art with regard to applying FPGAs in vehicular systems.